Tumor-infiltrating lymphocytes in triple negative breast cancer - L. M. Zakhartseva; M. O. Yanovytska (Zaporozhye State Medical University, 2020)
The aim of this retrospective study is to assess the prognostic value of tumor-infiltrating lymphocytes in triple negative breast carcinomas that lack both estrogen, progesterone receptors and Her2 amplification. The group of triple negative carcinomas has worse survival rates than other molecular subgroups of breast cancer, but at the same time it is very heterogeneous, and therefore requires the search for additional prognostic factors to improve the prognosis of patients. Materials and methods. The study included 350 samples of biopsies and surgical material from patients with stage I-III triple negative breast cancer who had not previously received chemotherapy. The median follow-up was 3.8 years for overall survival and 3.2 years for relapse-free survival. The prognostic value of tumor-infiltrating lymphocytes was evaluated by Kaplan-Meyer survival curves with a log-rank test, and one- and multifactor regression analysis according to the proportional risks Cox model. Results. Kaplan-Meier survival curves showed statistically significant relationships between tumor-infiltrating lymphocytes and overall and recurrence-free survival with a general trend to improve data for tumors with high lymphocyte volume. Proportional risks Cox model showed that tumors with a high number of tumor-infiltrating lymphocytes have statistically significantly better overall and recurrence-free survival rates (compared with tumors with a low number of tumor-infiltrating lymphocytes). The Kappa coefficient for interobserver variability was 0.79. It indicates a high level of agreement between pathologists in the evaluation of histological material. Conclusions. The high number of tumor-infiltrating lymphocytes in triple negative breast cancers is statistically significantly associated with better overall and recurrence-free survival rates. Assessment of tumor-infiltrating lymphocytes is rapid and does not require additional training, which makes this prognostic marker convenient to use.